Pemberian Air Sistem Gilir Berselang pada Saluran Sekunder Kandanghaur, Seksi Patrol, Perum Jasa Tirta II - - Subari; Muhammad Muqorrobin (Balai Teknik Irigasi, 2013)
Irrigation water delivery problems with insufficient water availability K factor less then 50 %is one issue of critical operations of irrigation system. It should be kept and looked for the best possible solution, both on water availability, irrigation system conditions, ability of soil to store water and irrigation operations and the partisipation of public / P3A. Therefore, this assessment using primary and secondary data were then calculated, and evaluation. By using water availability and soil physical conditions, can be determined how or water delivery at system. Based on the results of studies and field observations, the area gets irrigation water from the Kandanghaur secondary canal, Section Patrol, Gabus Wetan Water Master.Water distribution can done intermitent, with the re-provision of water for a period of 11 days.